2019
DOI: 10.3906/vet-1812-73
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics and fatty acid profiles of Bafra, Akkaraman, andBafra × Akkaraman F1 lamb meat

Abstract: Introduction Meat is a valuable part of human nutrition and a key factor in a balanced diet owing to its components. It provides high quality protein and fat also essential micronutrients that include iron, zinc, B vitamins, selenium, and phosphorus for optimal human health. Lamb is one of the red meat production sources, along with beef and pork. Lamb meat production is profitable if high quality pastures and suitable genotypes are available. The saleable yield type from sheep varies according to the geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
3
4
2
Order By: Relevance
“…No significant differences were observed between breeds ( p > 0.05). The recorded ultimate pH was within the normal ranges for commercial meats [ 14 ], which were similar to those reported for lambs of different breeds in other studies [ 15 17 ]. The pH evolution in postmortem is an essential determinant of organoleptic meat quality (color, juiciness, and tenderness), because it has a direct effect on meat functional proprieties, closely associated with meat biochemical process evolved after slaughter [ 18 ].…”
Section: Resultssupporting
confidence: 87%
“…No significant differences were observed between breeds ( p > 0.05). The recorded ultimate pH was within the normal ranges for commercial meats [ 14 ], which were similar to those reported for lambs of different breeds in other studies [ 15 17 ]. The pH evolution in postmortem is an essential determinant of organoleptic meat quality (color, juiciness, and tenderness), because it has a direct effect on meat functional proprieties, closely associated with meat biochemical process evolved after slaughter [ 18 ].…”
Section: Resultssupporting
confidence: 87%
“…Regarding the sums of DFA, the results show a significant difference (p < 0.01), with higher values recorded in the meat of Ti lambs (72.71 %). Our results are similar to those reported by Costa et al (2018) for lambs in Brazil (72.3 %), to those reported by Yaranoglu and Ozbeyaz (2019) for Turkish lambs (70.64 %-72.10 %), and to the values reported by Banskalieva et al (2000) for lamb meats (63.97 %-71.81 %). However, they are higher than those reported by Díaz et al (2003) for Manchega lambs (42.3 %).…”
Section: Fatty Acid Profile and Cholesterol Contentsupporting
confidence: 91%
“…They reported that, in a normal case, the ratio (C18 : 0 + C18 : 1)/C16 : 0 found in the literature ranged between 2 and 3 for lamb meat. Thus, our results are comparable to those reported by Liu et al (2015) and Yaranoglu and Ozbeyaz (2019) for Oula lambs (1.75-2.46) and for Turkish lambs (2.49-2.67), respectively. Regarding the sums of DFA, the results show a significant difference (p < 0.01), with higher values recorded in the meat of Ti lambs (72.71 %).…”
Section: Fatty Acid Profile and Cholesterol Contentsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the stearic acid is poorly digested and can be converted to oleic acid by the desaturase enzymes action. The SFA recorded value is lower than those reported for several sheep meats; Budimir, Trombetta [21] for Bergamasca lambs (50.91-55.68%), Belhaj, Mansouri [22] for Beni-Guil breed (49.45%) and Yaranoglu and Ozbeyaz [23] for two Turkish breeds (42.44-44.11%). In the present study, the most abundant PUFAs are Linoleic acid (LA: 11.40%) and Arachidonic acid (ARA: 5.52%).…”
Section: Fatty Acid Profilecontrasting
confidence: 63%